Clinical, clinicopathologic, histopathologic and immunohistochemical features of dogs with chronic enteropathy with and without concurrent protein-losing enteropathy: focus on the intestinal lymphatic vasculature - Wennogle, Sara Anne Jablonski, author; Webb, Craig, advisor; Ehrhart, EJ, committee member; Lappin, Michael, committee member; Twedt, David, committee member (Colorado State University. Libraries, 2018)
Chronic enteropathy (CE) is a term used to describe a group of chronic intestinal conditions in the dog that may respond to a variety of therapies including food, antibiotics, glucocorticoids, and immunosuppressives. Idiopathic CE is diagnosed after exclusion of extra-intestinal, infectious, parasitic, neoplastic and mechanical causes of gastrointestinal signs. Chronic enteropathies are often associated with histologic evidence of inflammation in the small intestine. In up to 20% of cases of CE with histologic evidence of inflammation in the small intestine, intestinal protein-loss occurs, a condition termed protein-losing enteropathy (PLE). Although several previous studies have identified the development of protein loss as a negative prognostic indicator in dogs with CE, the exact reasons why some dogs with CE develop concurrent PLE while others do not is not well understood. The goal of this work was to examine clinical, clinicopathologic, histopathologic, and immunohistochemical features of dogs with CE with and without PLE, with a special focus on the role of the intestinal lymphatic vasculature in cases of CE. In the first part of this work, we retrospectively examined histologic findings in a group of dogs with CE, and compared those findings between hypoalbuminemic and normoalbuminemic dogs. We found that many histopathologic features of idiopathic CE differed between dogs that were hypoalbuminemic versus those that were normoalbuminemic. Specifically, villous stunting, epithelial injury, crypt distension, lacteal dilation, intraepithelial lymphocytes, and lamina propria neutrophils were more common in hypoalbuminemic dogs with CE when compared to normoalbuminemic dogs with CE. We concluded that histopathologic features differ between hypoalbuminemic and normoalbuminemic dogs with CE and suggested that additional work is necessary to elucidate the clinical relevance of these differences. In particular, we noted that the high prevalence of lacteal dilation in hypoalbuminemic dogs with a primary diagnosis of inflammatory CE may be important and warranted further investigation. Next, we set out to prospectively evaluate whether a novel dietary approach could result in clinical improvement in dogs with CE and PLE who were not responding well to traditional therapy with glucocorticoids. We found that 8/10 dogs in the study achieved a complete clinical remission following a novel therapeutic dietary approach, with 7/8 dogs remaining in remission up to 3.5 years following the initial dietary change. Because 7/8 dogs that achieved a complete remission had been switched to a more fat-restricted diet than what they had previously been fed, we hypothesized that dietary fat-restriction may have played a role in their improvement. Because most of these dogs had not been diagnosed with lymphangiectasia, we speculated that the presence or extent of lymphatic abnormalities could have been underappreciated on routine histopathologic exam in this group of dogs. Lymphatic endothelial cell (LEC) immunohistochemical markers have identified intestinal lymphatic vasculature abnormalities in humans with inflammatory bowel disease (IBD). In the next chapter of our work, we utilized LEC markers and immunohistochemistry to evaluate the intestinal lymphatic vasculature in a group of dogs with CE. We uncovered significant mucosal lymphatic distension in some dogs with CE, most striking of which was in the ileum of dogs with CE and concurrent PLE. Several of these dogs did not have significant villous lymphangiectasia, therefore we concluded that routine histopathologic examination likely underestimated their lymphatic abnormalities. We also found that various abnormalities of the lymphatic vasculature were correlated with serum albumin levels. Finally, we aimed to improve our understanding of the pathogenesis of low serum vitamin D in dogs with CE. We did this by evaluating a variety of variables we felt could be associated with the mechanisms of low serum vitamin D in dogs with CE. We found that higher canine chronic enteropathy clinical activity (CCECAI) scores and serum CRP concentrations, and lower serum Vitamin E, cholesterol, and albumin concentrations were more likely in dogs with CE and low serum 25- hydroxyvitamin D (25[OH]D) concentrations compared to dogs with CE and normal serum 25(OH)D concentrations. In addition, histopathologic morphologic scores as well as overall WSAVA scores were correlated with serum 25(OH)D levels. Of particular relevance to this body of work were the findings of lower serum cholesterol and Vitamin E concentrations in dogs with low serum 25(OH)D and CE compared to dogs with normal 25(OH)D levels and CE. We concluded that the mechanism of low serum 25(OH)D in dogs with CE is likely multifactorial but fat malabsorption due to a variety of causes, including lymphatic dysfunction, could play a major role in the development of low 25(OH)D in this population. The work described in this dissertation has increased our understanding of protein-losing enteropathy as a consequence of canine CE, and in particular has highlighted the role of the intestinal lymphatic vasculature in these cases. This work can help to improve the lives of dogs suffering from CE and PLE and provides a solid foundation for further research in this arena.
Keywords: hypoalbuminemia; protein-losing enteropathy; chronic enteropathy; vitamin D; intestinal lymphatics